Environmentalism in Patricia Daniele’s the Girl Who Tested the Waters : A Qualitative Content Analysis - Alifah, Widya Nur (Fakultas Ilmu Budaya, 2026)
This study examines the environmental movement in the children’s book The Girl Who Tested the Waters 2025 by Patricia Danielle. Using Greg Garrard’s ecocritical approach and Krippendorff’s content analysis technique, the researcher analyses how the environmental movement is represented and how institutions can be involved in solving environmental problems. Both verbal and visual data were carefully examined using ecocritical theory by applying a coding framework based on Greg Garrard’s seven concepts. The results indicate that the environmental movement in the book is portrayed as an effort to protect the environment and resolve environmental issues through scientific knowledge and institutional involvement. Several of the codes analysed indicate that the INS-REP (Institutional Representation) code is the most dominant, suggesting that institutions also play a significant role in environmental issues. Ellen Swallow is portrayed as an agent of an institution that serves as an intermediary between scientific knowledge and her actions to resolve environmental problems, as she possesses ecological awareness and knowledge related to nature. In conclusion, the narrative of the book The Girl Who Tested the Waters presents the “cornucopia” position, which posits that environmental degradation will not stop, but that humans can resolve it. It also portrays environmentalism as a structured approach, one with clear processes, actions, and roles that is science-based and supported by the role of formal institutions in addressing environmental issues.
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Children's literature; content analysis; ecocriticism; environmentalism; picturebook.